Sociopreneurship and Spiritual Fundraising in Islamic Economics: A Case Study of Bubur Sedekah in Surakarta - Ade Yuliar; Agus Wahyu Triatmo; Supandi Supandi; Dita Andraeny (Yayasan Rahmat Islamiyah, 2026)
The phenomenon of Bubur Sedekah conducted by micro, small and medium enterprises (MSMEs) in Surakarta shows a close relationship between economic activities and social values. This study aims to examine whether the practice of sharing food in the form of Bubur Sedekah is a form of donation or an emotionally designed fundraising strategy to build a positive image and public loyalty. Using a qualitative approach and case studies of several businesses in urban and semi-urban areas, data were collected through in-depth interviews, participatory observation, and digital documentation. The results show that Bubur Sedekah is not only seen as a religious charity or donation intention, but also functions as soft marketing that is able to touch people's empathy, increase trust, and encourage participation in socio-economic activities. These findings strengthen the concept of sociopreneurship as a business model that combines humanitarian values and charitable sustainability through fundraising. This research recommends the need to develop ethical communication strategies so that the value of sincerity is maintained amid the potential commercialisation of social action.